Effect of ammonium polyphosphate and melamine pyrophosphate on fire behavior and thermal stability of unsaturated polyester synthesized from poly(ethylene terephthalate) waste - Nguyen, ThuHien; Hoang, DongQuy; Kim, Jinhwan (Macromolecular research, 2018)
The fire behavior and thermal stability of unsaturated polyester prepared from recycled poly(ethylene terephthalate) (RUP) in the present of two phosphorus-nitrogen flame retardants (FRs) including ammonium polyphosphate (APP) and melamine polyphosphate (MPP) have been investigated. The effectiveness of FRs on the fire proofing of material was test by UL-94 vertical classification and limiting oxygen index (LOI). The obtained data showed that the fire retardancy and thermal stability were remarkably enhanced with addition of FRs. The best grade of UL-94V standard, V-0 ranking was attained as loading of 25 wt% of APP or 30 wt% of MPP. LOI significantly were enhanced from 20 to 36%. Fourier transform infrared spectroscopy (FTIR), X-ray photoelectron spectroscopy (XPS), and Scanning electron microscope (SEM) were applied to determine the structure and morphology of char layers of RUP and RUP/FR mixtures. Thermogravimetric analysis (TGA) method was applied to investigate thermal stability of neat RUP, FRs, and RUP/FR and to evaluate kinetic parameters of the decomposition of RUP/FR. The mechanism of action of FRs, schemes for the possible decomposition mechanism RUP and FRs, and the cooperation of matrix and additives were also discussed.